THE STUDY OF BODY CONDITIONS OF HOLSTEIN - FRISIAN COWS IN THE FIRST 80 DAYS OF LACTATION - I. BENCSIK; N. PĂCALĂ; D. DRONCA; ADRIANA MOLDOVAN (Scientific Papers Animal Science and Biotechnologies, 2023)
Body condition represents the physiological and maintenance stage of an animal at a given time. The study on the body condition of the cows was conducted on a group of 22 Frisian Holstein cows. The average milk production per normal lactation (305 days) was 8664 kg. The animals were bred in free stall, stand for milking type 5x1. The body condition was assessed after calving (postpartum) and 80 days later. The body condition index decreased by 26, 39% in this time interval, achieving the critical score of 2.5 points. The production of milk represented the 27, 64±0, 98% of the total average milk production. The appreciation of the body condition using the point method represents and easy method. The appreciation of the body condition by the point method represents a valuable tool for the health monitoring and proper nutrition of cows with superior genotypes.